Design of a microkernelbased services manager for IoT with isolated processing - Jose Antonio Ortega-González; Luis G. León-Vega (Tecnología en Marcha, 2022)
The development of projects related to the Internet of Things has generated a significant impact on the growth of the software industry. Although there are several alternatives to their development, users are limited by inherent factors, such as vendor lock-in, software development flexibility, and security. This article shows a platform design that provides a deployment and management system for IoT projects avoiding some of the limitations of the current tools, such as vendor lockin and limitations in the development technologies.